BDNF: A Key Regulator for Protein-synthesis Dependent LTP and Long-term Memory? - Lu, Yuan (2007)
It is generally believed that late-phase long-term potentiation (L-LTP) and long-term memory (LTM) require new protein synthesis. Although the full complement of proteins mediating the long-lasting changes in synaptic efficacy have yet to be identified, several lines of evidence point to a crucial role for activity-induced brain derived neurotrophic factor (BDNF) expression in generating sustained structural and functional changes at hippocampal synapses thought to underlie some forms of LTM. In particular, BDNF is sufficient to induce the transformation of early to late phase LTP in the presence of protein synthesis inhibitors, and inhibition of BDNF signaling impairs LTM. Despite solid evidence for a critical role of BDNF in L-LTP and LTM, many issues are not resolved. Given that BDNF needs to be processed in Golgi outposts localized at the branch point of one or few dendrites, a conceptually challenging problem is how locally synthesized BDNF in dendrites could ensure synapse-specific modulation of L-LTP. An interesting alternative is that BDNF-TrkB signaling is involved in synaptic tagging, a prominent hypothesis that explains how soma-derived protein could selectively modulate the tetanized (tagged) synapse. Finally, specific roles of BDNF in the acquisition, retention or extinction of LTM remain to be established.